Survival to starvation of the house fly, Musca domestica L. and blow fly, Chrysomya megacephala (F.) - Bunchu, Nophawan; Piangjai, Somsak; Sukontason, Kabkaew L.; Sukontason, Kom (Biomedical Sciences and Clinical Medicine, 2024)
Flies deprived of food for 24 hours are used the most in studies of fly behaviour and suitable attractants when searching for appropriate bait. However, each fly species may tolerate starvation differently, and no study has shown survival to starvation clearly for the housefly, Musca domestica L. or blowfly, Chrysomya megacephala (F.). Therefore, this study investigated the survival to starvation of both species (3-days-old). Survival was recorded after 24, 48 and 72 hours of experimental time. The survival of male and female food-deprived M. domestica was signifi cantly lower than a control group of normal-fed flies [10% (w/v) sugar solution mixed with 1.5% (v/v) multivitamin syrup]. At 24 hours, the survival of male food-deprived M. domestica rapidly decreased to 2 fold lower than food-deprived females, and 2.5 fold lower than normal-fed females. Additionally, all male and female food-deprived M. domestica had died at 72 hours, while most of the normal-fed flies (98-100%) were still alive. Regarding C. megacephala, the survival of male and female food-deprived flies was similar to that of M. domestica. At 24 hours, no signifi cant difference was observed between the survival of food-deprived and normal-fed C. megacephala flies. In contrast, survival of food-deprived males and females decreased by more than 60% that of normal-fed flies at 48 hours. At 72 hours, almost all of the food-deprived flies had died, whereas most of the control flies were still alive, which corresponded with flies of M. domestica. In conclusion, more C. megacephala of both sexes survived to starvation than M. domestica males and females, and more M. domestica females survived to starvation than males. These results showed that using a time span to starve flies prior to their use in experiments, particularly those for behavioral observation, would rely on the species and gender of the fly.